The Intranasal Administration of Transferrin‐Loaded Extracellular Vesicles Enhances Remyelination - Mattera, Vanesa Soledad (2025)
Oligodendrocytes (OLs), the myelinating glial cells of the central nervous system (CNS), are impaired in demyelinating diseases such as multiple sclerosis (MS). OL loss is characterized by inflammation, immune cell activity, and a failure of remyelination due to oligodendrocyte dysfunction and death, ultimately leading to demyelination and axonal damage. Given their central role in maintaining CNS integrity, therapeutic strategies aimed at protecting or restoring OL function are essential. Moreover, the limited permeability of the blood–brain barrier to many therapeutic compounds remains a major challenge, highlighting the need for innovative delivery approaches. Among these, the intranasal (IN) route has emerged as a promising noninvasive strategy for targeting the CNS. Within this therapeutic framework, Transferrin (Tf), a glycoprotein involved in iron homeostasis, has been shown to promote both developmental myelination and remyelination by redistributing and delivering iron, an essential cofactor for OL maturation and oxidative metabolism. In parallel, extracellular vesicles (EVs) have gained increasing attention as mediators of intercellular communication and potential drug delivery vehicles to the brain, offering advantages such as minimal immunogenicity, efficient cellular uptake, and cargo protection from degradation. In this review, the potential of EVs as biological carriers of molecules to promote remyelination is discussed, with a particular focus on Tf delivered via the intranasal route, as well as the cellular mechanisms underlying this internalization.